The Effect Of Locus Of Control And Equity Sensitivity On The Effect Of Accountants' Ethical Behavior (Empirical Study At A Public Accounting Firm In Medan City) - Aulia Ulfa Ramadhani; Riva Ubar Harahap (Proceeding International Seminar of Islamic Studies, 2019)
This research was conducted to see the effect ofLocus Of Control and Equity Sensitivityon Accountants' Ethical Behavior partially and simultaneously. This research is associative, ie research conducted to see the effect of one or more variables with other variables. The population used in this study were all public accountants who worked in public accounting firms in Medan City. The sampling technique used is saturated sampling. The data collection technique used in this study was to distribute questionnaires to research respondents. The data analysis method used is multiple linear analysis. The results of the study are as follows: (1)Locus Of Controlpositive and significant effect on the Ethical Behavior of Accountants, (2)Equity Sensitivityno positive and significant effect on the Ethical Behavior of Accountants, (3)Locus Of ControlandEquity Sensitivitysimultaneously influence the Ethical Behavior of Accountants.